Molecular mechanism of ATF6 in unfolded protein response and its role in disease - Yingying Lei; Hong Yu; Shaoxue Ding; Hui Liu; Chunyan Liu; Rong Fu (Heliyon, 2024)
Activating transcription factor 6 (ATF6), an important signaling molecule in unfolded protein response (UPR), plays a role in the pathogenesis of several diseases, including diseases such as congenital retinal disease, liver fibrosis and ankylosing spondylitis. After endoplasmic reticulum stress (ERS), ATF6 is activated after separation from binding immunoglobulin protein (GRP78/BiP) in the endoplasmic reticulum (ER) and transported to the Golgi apparatus to be hydrolyzed by site 1 and site 2 proteases into ATF6 fragments, which localize to the nucleus and regulate the transcription and expression of ERS-related genes. In these diseases, ERS leads to the activation of UPR, which ultimately lead to the occurrence and development of diseases by regulating the physiological state of cells through the ATF6 signaling pathway. Here, we discuss the evidence for the pathogenic importance of ATF6 signaling in different diseases and discuss preclinical results.